Analisis Kinerja Anggaran Pendapatan dan Belanja Daerah pada Pemerintah Daerah Kabupaten Subang Sebelum dan Saat Pandemi Covid-19 - Mutia Agnika; Sugih Sutrisno Putra; Sudradjat (Indonesian Accounting Research Journal, 2021)
The Covid-19 pandemic has had a major impact on the country's economy, especially on state incomes and expenditures. To save the economy, the government issues various financial policies that will also have an impact on the realization of the Religional Income and Expenditure Budget (APBD). This study aims to determine the performance of the Subang Regency APBD before and during the Covid-19 pandemic. This study uses a quantitative descriptive method by calculating quantitative data from the Subang Regency LRA for Fiscal Years 2019 and 2020, using an analysis of regional financial performance which includes the regional financial independence ratio, PAD effectiveness ratio, regional financial efficiency ratio, compatibility ratio, and growth ratio. The results show that the performance of the Subang Regency APBD in 2019 and 2020 seen from the regional financial independence ratio is very low, the PAD effectiveness ratio is quite effective, the regional financial efficiency ratio has changed from inefficient to efficient, the compatibility ratio is dominated by the operating expenditure ratio compared to the capital expenditure ratio in reasonable proportions, as well as growth ratios that experienced negative growth.